The Digestive Tract Morphology and Clark index of Mud Sleeper Butis koilomatodon Living in some Coastal and Estuarine areas belonging to Tra Vinh, Soc Trang, Bac Lieu and Ca Mau - Quang, Dinh Minh; Nha Y, Nguyen Thi; Huyen Tran, Lam Thi; Gieo, Phan Thanh (VNU Journal of Science: Natural Sciences and Technology; Vol 36 No 3DO - 10.25073/2588-1140/vnunst.5051, 2020)
This study provides new data on the characteristics of the gastrointestinal morphology and the variation of Clark index according to sexes, fish size groups, seasons and sampling sites of mud sleeper Butis koilomatodon , one of the commercially valuable gobiid species in the Mekong Delta. Analytical results of 1,227 fish samples collected monthly from April 2019 to March 2020 in Duyen Hai (Tra Vinh), Cu Lao Dung (Soc Trang), Tran De (Soc Trang), Hoa Binh (Bac Lieu), Dong Hai (Bac Lieu) and Dam Doi (Ca Mau) showed that this species had a slightly sloping mouth, the length between two jaws was relatively equal, teeth were small and grew in long lines on both jaws with the outer row having larger teeth. The length of the gut was shorter than the total length of the fish and so this species belonged to predator group. The Clark index depended on length of fish, sampling time and site but excluding season and gender. It was also effected by interactions of fish length x season; fish length x site and season x site. Conversly, the interactions of gender x season and gender x site did not impact on the Clark index. The outcomes of research will provide useful data in artificial aquaculture Butis koilomatodon .